2022
DOI: 10.3390/antiox11102013
|View full text |Cite
|
Sign up to set email alerts
|

2-Methoxyestradiol Damages DNA in Glioblastoma Cells by Regulating nNOS and Heat Shock Proteins

Abstract: Gliomas are the most prevalent primary tumors of the central nervous system (CNS), accounting for over fifty percent of all primary intracranial neoplasms. Glioblastoma (GBM) is the most prevalent form of malignant glioma and is often incurable. The main distinguishing trait of GBM is the presence of hypoxic regions accompanied by enhanced angiogenesis. 2-Methoxyestradiol (2-ME) is a well-established antiangiogenic and antiproliferative drug. In current clinical studies, 2-ME, known as Panzem, was examined for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…Apoptosis is a programmed cell death process that is considered one of the important mechanisms by which anti-tumor drugs exert their effects 51 . It involves the regulation of intracellular molecular signaling pathways, leading to characteristic changes such as DNA fragmentation, nuclear condensation, and membrane blebbing, ultimately resulting in cell death 52 . We found that in melanoma, FXT can induce mitochondria-mediated intrinsic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis is a programmed cell death process that is considered one of the important mechanisms by which anti-tumor drugs exert their effects 51 . It involves the regulation of intracellular molecular signaling pathways, leading to characteristic changes such as DNA fragmentation, nuclear condensation, and membrane blebbing, ultimately resulting in cell death 52 . We found that in melanoma, FXT can induce mitochondria-mediated intrinsic apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…One of the cytostatic mechanisms of action of 2-ME2 in the experimental models is the arrest of cells in the subG1 phase, which suggests the induction of apoptosis. Additionally, 2-ME2 was also found to increase the cell quantity in the subG1 phase in other neural cells [ 11 , 47 ]. The increase in the number of apoptotic cells noted across a panel of concentrations corresponding to both pharmacological and physiological levels was observed.…”
Section: Discussionmentioning
confidence: 99%
“…2ME2 inhibits mitosis in cancer cells by binding to tubulin at the colchicine binding site, affecting microtubule assembly dynamics and mitotic spindle assembly and thus interfering with cell cycle progression [16]. Recent report has identi ed the inhibitory effect of 2ME2 on nNOS and heat shock protein through DNA damage in glioblastoma cells [43]. Also, Zhang et al (2023) have identi ed new perspective of effects of 2ME2 in progression of Non-small cell lung cancer (NSCLC) through inhibition of circ_0010235/miR-34a-5p/NFAT5 axis [44].…”
Section: Discussionmentioning
confidence: 99%